1989
DOI: 10.3346/jkms.1989.4.4.185
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between electrophysiologic and morphologic changes in lead induced peripheral neuropathy in rats

Abstract: Compound nerve action potential (CNAP) of the mixed peripheral nerve is composed of A alpha beta, A delta, and C potentials. All components of CNAPs in the sciatic nerve were recorded by stimulating the tibial nerve of both control and lead-poisoned rats. Marked decrease of nerve conduction velocity and prolonged duration were found in A alpha beta and A delta fibers especially in large myelinated A alpha beta fibers. The amplitude decreased in A alpha beta potential, but the area did not change. In C potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Despite these deficiencies, studies in animal models have confirmed the neurotoxicity and nephrotoxicity of lead and its capacity to disturb iron and copper metabolism in haemopoiesis and calcium, zinc and magnesium in epithelial cell differentiation. 42,[59][60][61][62][63][64][65] Experimental evidence is available also to show that lead intoxication is associated with osteological abnormality and defects in mineralisation through inhibition of alkaline phosphatase and other key enzymes involved in calcium metabolism. 66,67 Experimental studies in rodents provide strong evidence that certain lead compounds should be considered carcinogenic following oral or in-diet administration, and through parenteral administration.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Despite these deficiencies, studies in animal models have confirmed the neurotoxicity and nephrotoxicity of lead and its capacity to disturb iron and copper metabolism in haemopoiesis and calcium, zinc and magnesium in epithelial cell differentiation. 42,[59][60][61][62][63][64][65] Experimental evidence is available also to show that lead intoxication is associated with osteological abnormality and defects in mineralisation through inhibition of alkaline phosphatase and other key enzymes involved in calcium metabolism. 66,67 Experimental studies in rodents provide strong evidence that certain lead compounds should be considered carcinogenic following oral or in-diet administration, and through parenteral administration.…”
Section: In Vitro Studiesmentioning
confidence: 99%